Memorias del arzobispado de Tarragona (siglos XII-XIII): Memories of the Archbishopric of Tarragona (12th-13th Centuries) - Bonet Donato, María (Aragón en la Edad Media, 2020)
Abstract: These pages explain the making of an episcopal identity story. The medieval archbishopric of Tarragona wove a specific memory on episcopal authority, that defined a sacred identity, linked to the first Peninsular Christianization and with singular mechanisms of power. This tradition of the episcopal see was constructed contemporary and reinforced in subsequent times. Some key elements of these memories were: the restoration of the late-Roman Church, the sacred nature of the seat and of some bishops, the vindication of metropolitan and ‘first’ see, the religious authority in the region and against other powers, the recognition of pontifical support and patronage, the links with the major political powers, the religious charismae and the features of lordly power. In short, the archbishop’s power was supported by the tradition of the see and drew on a set of iconic images that became a story of legitimacy and authority. Key words: memory, church history, historiography, archbishopric of Tarragona, 12th-13th centuries. Resumen: El arzobispado medieval de Tarragona tejió una memoria sobre su autoridad, revestida de una identidad sagrada, que difundió los caracteres específicos de su potestad y de la realidad dominical. Las tradiciones sobre la sede tarraconense fueron establecidas durante los siglos xii y xiii, con aportaciones destacadas como la del prelado Benet de Rocabertí. Algunos elementos laudatorios y reivindicativos de sus mensajes fueron: la vinculada a la primera cristianización peninsular, la restauración de la Iglesia romana tardía, la reclamación de la primacía, la naturaleza sagrada de algunos obispos, la preminencia en la jurisdicción religiosa y dominical, el reconocimiento del apoyo y patrocinio pontificio y los carismas religiosos. En resumen, el poder del arzobispo se dotó de una ideología que se apoyó en un conjunto de imágenes icónicas al servició de una narrativa legitimadora y para la afirmación de los poderes y las proyecciones de la mitra. Palabras clave: memoria, historia de la iglesia, historiografía, arzobispado de Tarragona, siglos xii-xiii.